The inscribed silver disc brooch from the Tuukkala cemetery in Mikkeli - Moilanen, Ulla (Svenska Litteratursällskapet I Finland, 2025)
The silver disc brooch found in the Tuukkala inhumation cemetery in Mikkeli in 1886, dated to the twelfth or thirteenth century, is one of very few Late Iron Age artefacts found in Finnish territory that contain Scandinavian runic inscriptions. The inscriptions occur in two locations on the reverse of the brooch and the carvings appear to form a typical owner inscription. The text contains at least one, or probably two, proper names, and microscopic examination of the brooch indicates that the texts were probably made with different implements. Because the brooch is a stray find from a cemetery, the exact location of which was destroyed before excavation, closer examination of the individual with whom the artefact was buried is not possible. The runic inscriptions and various traces of repairs visible on the brooch, however, point to a long period of use and possible changes in the significance of the object over its lifespan
Runes in Finland